2012
DOI: 10.1186/gb-2012-13-9-r80
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of intracellular pH reveals quantitative control of cell division rate by pHc in Saccharomyces cerevisiae

Abstract: BackgroundBecause protonation affects the properties of almost all molecules in cells, cytosolic pH (pHc) is usually assumed to be constant. In the model organism yeast, however, pHc changes in response to the presence of nutrients and varies during growth. Since small changes in pHc can lead to major changes in metabolism, signal transduction, and phenotype, we decided to analyze pHc control.ResultsIntroducing a pH-sensitive reporter protein into the yeast deletion collection allowed quantitative genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
160
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(181 citation statements)
references
References 66 publications
(90 reference statements)
20
160
0
1
Order By: Relevance
“…Our first approach was to determine whether the intracellular acidification caused by the four weak acids could be considered the main mechanism of growth inhibition, as the pH i was shown to be in control of growth rate in nonstressed cells (34). Addition of weak acids to growing cells instantly acidified the cells, after which the pH i recovered to various extents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first approach was to determine whether the intracellular acidification caused by the four weak acids could be considered the main mechanism of growth inhibition, as the pH i was shown to be in control of growth rate in nonstressed cells (34). Addition of weak acids to growing cells instantly acidified the cells, after which the pH i recovered to various extents.…”
Section: Discussionmentioning
confidence: 99%
“…At the near-to-neutral cytosolic pH during exponential growth on glucose (33), the acid dissociates to generate protons and anions, which are charged and therefore cannot simply diffuse back out. This causes intracellular acidification and anion accumulation, both of which impede metabolic function (23,34,35). Indirect consequences of weak acid stress are oxidative damage (41) and an inferred perturbation of the plasma membrane (47,50).…”
mentioning
confidence: 99%
“…For example, cells accumulate storage carbohydrates trehalose and glycogen (41). Medium composition also strongly affects pH i (42). Conversely, cells that are transferred from an exponential culture to a fresh medium without glucose are confronted with a different environment (i.e., different pH ex and nutrient availability).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, by being able to pump protons, are an important component of the emerging "metabolic" signal mediated by cytosolic pH. A genome-wide screening of S. cerevisiae knockout mutants revealed that kcs1 has one of the lowest cytosolic pH and its metabolic rate is virtually unaffected by lowering medium pH [63]. With this in mind, the altered mitochondria functionality of ip6k1 -/-mice might explain the inability of these mice to become obese [64].…”
Section: Inositol Pyrophosphates As Metabolic Regulatorsmentioning
confidence: 99%